2022
DOI: 10.1038/s41598-022-14419-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic profiling of peptidase expression in Fasciola hepatica eggs developing at host’s body temperature

Abstract: Fasciola hepatica is a global parasite of livestock which also causes a neglected zoonosis in humans. The parasite’s communication with the host during its complicated lifecycle is based on an ingenious enzymatic apparatus which includes a variety of peptidases. These enzymes are implicated in parasite migration, pathogenesis of the disease, and modification of host immune response. Although the dynamics of proteolytic machinery produced by intra-mammalian F. hepatica life stages has been previously investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…In agreement with the study by Ilgová et al [ 30 ], we observed that the eggs express a more dynamic range of peptidases and peptidase inhibitors, and this is also exhibited by the miracidia and rediae. This analysis is also consistent with the transcriptome analysis by Zhang et al [ 26 ] that described an upregulation of peptidase inhibitors in the egg transcriptome, and an enrichment of zinc ion binding and metallo-endopeptidase activity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with the study by Ilgová et al [ 30 ], we observed that the eggs express a more dynamic range of peptidases and peptidase inhibitors, and this is also exhibited by the miracidia and rediae. This analysis is also consistent with the transcriptome analysis by Zhang et al [ 26 ] that described an upregulation of peptidase inhibitors in the egg transcriptome, and an enrichment of zinc ion binding and metallo-endopeptidase activity.…”
Section: Discussionsupporting
confidence: 93%
“…Despite observing lower transcriptional levels of metallopeptidase inhibitors (I63) in F. hepatica eggs compared to F. gigantica , protein products of these genes are abundant within the F. hepatica egg somatic proteome. It is worthwhile noting, however, as highlighted in the study by Ilgová et al [ 30 ], that Fasciola eggs are laid unembryonated and as the eggs develop, their transcriptional and protein profiles change.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations